MANAGEMENT OF QUALITY IMPROVEMENT IN LEARNING BASED ON DIGITALIZATION AT MADRASAH UMMUL QURO AT-TARBAWIYAH PUTRI PLAKPAK PEGANTENAN PAMEKASAN - Fahmi, Ach. Syafiq Fahmi; Fathor Rosid; Ali Nurhadi; Abdul Aziz; Abdul Wahid (re-JIEM (Research Journal of Islamic Education Management), 2024)
This research aims to explore the implementation, results, and supporting and inhibiting factors of digitalization-based learning quality improvement management implemented at Madrasah Ummul Quro At-Tarbawiyah Putri. This research was conducted using a qualitative model with a variety of case study approaches. The results of this research show that the implementation of management to improve the quality of digitalization-based learning at Madrasah Ummul Quro At-Tarbawiyah Putri was carried out in three stages, namely planning, implementation and evaluation. The results of the management of improving the quality of digitalization-based learning are very visible, it is easier for teachers to convey learning, and female students can easily understand lessons related to visualization. Supporting factors in improving the quality of digitalization-based learning include developments in digitalization and the demands of the times, the availability of digital technology, and full support from the boarding school leadership, as well as the enthusiasm of the teacher council in improving the quality of learning. Meanwhile, the inhibiting factors are that the cost of providing digital facilities is very expensive, and teachers' digital literacy abilities are uneven.